Descriptors for Mangaba (Hancornia speciosa Gomes) - Silva Júnior, J.F. da; Muniz, A.V.C. da S.; Lédo, A. da; Maia, M.C.C.; Carvalhaes, M.A.; Silva, S.M da C.; Dulloo, Mohammad Ehsan; Alercia, A. (Bioversity International, 2018)
The ‘Descriptors for Mangaba (Hancornia speciosa Gomes)’ were developed by the Embrapa Tabuleiros Costeiros and a group of researchers from three research centres of the Brazilian Agricultural Research Corporation (Embrapa). Mangaba is a native fruit species of Brazil, but also occurs in Paraguay, Bolivia and Peru. The genus is monotypic, and there are six botanical varieties. H. speciosa var. speciosa is the most widely distributed occurring in the Cerrado, coastal tablelands and lowlands of Brazil. This neglected species, is considered one of the "Plants of the Future", a group of plants with a high priority for conservation, research and development in Brazil. Research on the genetic resources of underutilized native tropical species has been one of the main objectives of Bioversity International and Embrapa, and this list for mangaba contributes greatly to its characterization and, consequently, conservation and use activities. This document is a first approach for the definition of a descriptors list, aiming at supporting studies focusing on documenting characterization and evaluation traits and conserving its genetic resources, and, mainly, increasing production and use of nutritious mangaba products.